Public Communication Strategies in Sustainable Development Goals - Pratama, Inka Nusamuda; Darmansyah, Darmansyah; Subandi, Azwar; Ibrahim, Adil Hassan (Universitas Teuku Umar, 2024)
Policy communication is essential in building ideal governance. This research examines the public communication strategy carried out by Zulkieflimansyah as Governor of West Nusa Tenggara via his Twitter social media account (@bangzul_ntb) in formulating inclusive policies oriented towards Sustainable Development Goals with three sub-themes, namely healthy living, poverty alleviation and improving the quality of education. This research uses qualitative methods with the Qualitative Data Analysis (QDA) Miner approach used in the content, network, and cloud analysis using Nvivo 12 Plus software. The research results show that the Healthy Life context highlights progress in health policy and generates awareness regarding the positive correlation between health and economic growth. In efforts to eradicate poverty, concrete actions such as implementing inclusive programs and emphasizing local economic empowerment are conveyed via social media. Meanwhile, in the field of Improving the Quality of Education, Zulkieflimansyah guarantees access, improved facilities, scholarships, and the use of innovative technology. Its approach involving community participation forms an inclusive framework for enhancing the quality of education. Therefore, the strategic policies implemented by Zulkieflimansyah via his personal Twitter account reflect a holistic and sustainable approach to achieving inclusive goals and sustainable economic development.